ANALISIS HUKUM MENGENAI SANKSI PIDANA PENJARA SEUMUR HIDUP TERHADAP PELAKU TINDAK PIDANA PEMBUNUHAN BERENCANA DALAM PERSPEKTIF KRIMINOLOGI : STUDI PENGADILAN NEGERI MEDAN - Marihot Tua Silitonga; Ediwarman Ediwarman; Mahmud Mulyadi; Chairul Bariah (USU LAW JOURNAL, 2017)
ABSTRACT   People’s relevance in the social and national life starts from an understanding that law is a part of the inherent system in human life. Therefore, we need a policy to improve or make the national KUHP (the Criminal Code) as the value in the society in order that it better reflects the personality of Indonesian nation. Today, life imprisonment is still an alternative to the imposition of death penalty for murderers; thus, it is necessary that life imprisonment be regulated by taking into account the existing interests, the factors that cause and need to be considered in imposing criminal sanctions. The research discussed some problems i.e. how the legal provisions regulated the criminal sanctions for a premeditated murder, how the process leading to life imprisonment for the criminal of a premeditated murder in criminology perspective, how the legal policy on the criminal of a premeditated murder. The results show that firstly, criminal sanction for the criminal of a premeditated murder is stipulated in article 340 of KUHP regarding the pronouncing of death penalty, life imprisonment and 20 year imprisonment. In addition, regarding the offenses stipulated in KUHP, it also regulates the types and criminal sanctions in article 10 of KUHP which is in force at present time. Secondly, the Judge continues to use the factors that cause the occurrence of such crime, namely internal and external factors to be taken into consideration in pronouncing a criminal case of premeditated murder. Thirdly, the criminal law policy is oriented on the reality that the criminal law policy implemented takes into more consideration the criminal’s behaviour and fate that he will become better in the future. Keywords: Crime, Premeditated Murder, Criminology